ANALISIS KINERJA ORGANISASI DINAS LINGKUNGAN HIDUP KABUPATEN DEMAK DALAM PENGELOLAAN SAMPAH - Hardiyanti, Kiki; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Demak Regency is one of the districts in Central Java that is developing and is not spared experiencing waste problems. The Department of Environment Demak Regency is an agency responsible for handling the environment, one of which is waste management. The purpose of this study is to analyze and describe the performance of the environmental agency of Demak in waste management. The methods used in this research is descriptive qualitative. Indicators are used to assess performance are productivity, service quality, responsiveness, responsibility, and accountability. In addition, the assessment of performance seen from the driving factor and a barrier to the performance of the organization. The results of this research show that the productivity performance in waste management has not been fullest because of limited human resources, facilities and infrastructure and the efforts that have not been right. Quality of service is still not optimally and needs to be increased again. Responsiveness is not optimal because there are no facilities or activities to determine the community needs. Responsibility is not maximal because it is still only focused on the Kalikondang landfill and the fulfillment of infrastructure in the city, as well as the lack of transparency to the public. Leadership and team is the driving factor, while restricting factors include a lack of human resources, limitation of funds, and a shortage of facilities and infrastructure. The researcher's recommendation is to do a strategic effort in optimizing performance, improvement of facilities and infrastructure, as well as involve community.